Intermittent and increasing intravenous lipopolysaccharide effect on metabolism, inflammation, and production in lactating dairy cows - S. Rodriguez-Jimenez; E.A. Horst; E.J. Mayorga; M.A. Abeyta; B.M. Goetz; L.H. Baumgard (Journal of Dairy Science)
ABSTRACT: Experimental objectives were to create a chronic inflammatory model to evaluate the effects of persistent immune activation on metabolism, inflammation, and productivity in lactating dairy cows. Twelve lactating Holstein cows (631 ± 16 kg BW; 124 ± 15 DIM) were enrolled in a study with 2 experimental periods; during period 1 (P1; 5 d), cows were fed ad libitum and baseline data were obtained. At the initiation of period 2 (P2; 7 d), cows were assigned to 1 of 2 treatments: (1) saline infused and pair-fed (PF; 5 mL i.v. sterile saline on d 1, 3, and 5; n = 6) or (2) LPS infused and ad libitum fed (LPS; 0.2, 0.8, and 1.6 µg LPS/kg BW i.v. on d 1, 3, and 5, respectively; n = 6). Blood samples were collected on d 3 and 5 of P1, and d 1, 3, 5, and 7 of P2. Administering LPS induced a febrile response (∼6 h duration) following each bolus (+0.6, 0.6, and 0.8°C, for d 1, 3, and 5, respectively). Lipopolysaccharide binding protein, serum amyloid A, and haptoglobin concentrations increased in LPS-administered cows relative to baseline and PF animals. Cholesterol and albumin concentrations decreased in LPS relative to PF cows and effects were most prominent from d 3 to 7 of P2. Circulating cortisol in LPS-infused cows progressively increased during P2 (63% on d 7) relative to PF cows. Overall, during P2, LPS administration induced a sawtooth pattern in DMI and the negative consequences on DMI ameliorated as P2 progressed. By design, the DMI pattern in PF cows was similar to their LPS counterparts. Administering LPS also created a reciprocating response in milk yield that lessened as P2 progressed. Overall, milk yield was decreased in LPS and PF cows compared with P1 (29% and 10%, respectively). Circulating insulin decreased in both treatments relative to P1, but the decrease was more severe in PF (61%) compared with LPS-infused cows (27%). Relative to PF cows, nonesterified fatty acids (NEFA) remained similar to P1 in LPS-administered cows, but increased (3.2-fold) in PF cows. Ionized calcium decreased in LPS cows compared with PF controls. In summary, alternating and increasing LPS doses caused chronic inflammation, markedly altered metabolism, and temporarily decreased DMI and milk synthesis. However, although the acute phase proteins remained elevated throughout P2, the effect on production lessened with time.